Caracterização físico-mecânica e biológica de cimentos experimentais à base de MTA para o complexo dentino-pulpar - Dantas, Raquel Venâncio Fernandes (2011)
There is a need to develop new cements to optimize pulp therapy strategies. The aim of this study was evaluate physic-chemical and biological parameters of experimental cements (Hybrid, Paste and Resinous), including pH, diametral tensile strength and cytotoxicity of these experimental cements comparing them to MTA (Angelus®, Londrina, PR, Brazil) and a glass ionomer cement developed in our laboratory. For the physic-mechanical and biological tests specimens with standard dimensions were produced. For pH measurement, specimens were immersed in culture medium (DMEM) supplemented with FBS (fetal bovine serum) and analyzed by digital pH meter at 3, 24, 48 and 72h. For diametral tensile strength test the specimens were subjected to compressive load until the fracture. To evaluate cytotoxicity 3T3 cells were cultured and exposed to the cement eluates. The cell viability was detected using MTT test. The results were analyzed using analysis of variance (ANOVA) and Tukey's test (p <0.05). The Paste group showed pH values similar to the MTA, as well as the Hybrid group was similar to the GIC group (p> 0.05). All materials presented alkaline pH values or were near to neutrality on evaluated times. MTA and GIC showed similar strength results. The lowest and highest strength values were observed in groups Paste and Resinous, respectively (p <0.05). Cell viability for MTA, Hybrid, Paste and Resinous groups, were 49, 93, 90 and 86% respectively, when compared to the control group. Considering this in vitro study, we concluded that the photo-cured Resinous experimental cement presented a performance similar or superior to the commercial or other experimental materials tested